Effectiveness of a new triple-row circular stapler in reducing the risk of colorectal anastomotic leakage: A historical control and propensity score–matched study. Issue 27 (8th July 2022) - Mazaki, Junichi; Katsumata, Kenji; Ishizaki, Tetsuo; Fukushima, Noritoshi; Udo, Ryutaro; Tago, Tomoya; Kasahara, Kenta; Kuwabara, Hiroshi; Enomoto, Masanobu; Nagakawa, Yuichi; Tsuchida, Akihiko
Abstract : Anastomotic leakage (AL) after colorectal surgery is a serious complication. This study aimed to evaluate the effectiveness of the EEA™ circular stapler, a new triple-row circular stapler (TCS), relative to a conventional, double-row circular stapler (DCS). A total of 285 patients who underwent anastomosis with the double stapling technique at the Tokyo Medical University Hospital between 2017 and 2021 were included in this nonrandomized clinical trial with historical controls using a propensity score (PS) analysis. The primary endpoint was the risk of AL. We performed a 1:2 PS matching analysis. Before case matching, AL occurred in 15 (7.4%) and 2 (2.4%) patients in the DCS and TCS groups, respectively, with no significant difference ( P = .17). After case matching, AL occurred in 13 patients (11.6%) and 1 patient (1.8%) in the DCS and TCS groups, respectively, revealing a significant difference ( P = .04). Cox models were created by applying PS to adjust for group differences via regression adjustment. Odds ratios for AL in the DCS group versus the TCS group were 0.31 (95% confidence interval [CI]: 0.07–1.38) in the entire cohort, 0.15 (95% CI: 0.02–0.64) in the regression adjustment cohort, and 0.14 (95% CI: 0.02–1.09) in the 1:2 PS-matched cohort. PS analysis of clinical data suggested that the use of TCS contributes to a reduced risk of AL after colorectal anastomosis CTwith the double stapling technique.